How the other half works : immigration and the social organization of labor - Waldinger, Roger David (University of California Press, 2003)
How the other half works solves the riddle of America's contemporary immigration puzzle: why an increasingly high-tech society has use for so many immigrants who lack the basic skills that today's economy seems to demand. Waldinger and Lichter isolate the key factors that explain the presence of unskilled immigrants in our midst. Focusing on Los Angeles, the capital of today's immigrant America, this hard-hitting book elucidates the other side of the new economy, showing that hiring is finding not so much "one's own kind" but rather the "right kind" to fit the demeaning, but indispensable, jobs many American workers disdain